The influence of profitability, company dynamics and digital transformation on company value - Mustaqim, Hendri; Zuraida; Yusmita, Fifi (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2025)
This study examines the effect of profitability, company dynamics, and digital transformation on firm value, both simultaneously and partially, in mining companies listed on the Indonesia Stock Exchange (IDX). This research adopts a causal-explanatory approach using panel data regression analysis. The study population comprises mining sector companies listed on the IDX during the 2019-2022 period, with a total of 200 observations selected through purposive sampling based on specific criteria. The study utilizes secondary data sources. The results indicate that profitability, company dynamics, and digital transformation simultaneously have a significant effect on firm value. Partially, profitability shows a negative effect, while company dynamics have a positive effect on firm value. In contrast, digital transformation is found to have no significant impact on firm value in mining companies listed on the IDX. These findings highlight the importance of internal performance factors over digital initiatives in driving firm value within the mining sector.